Numerical investigations of wind and thermal environment in 2D scaled street canyons with various aspect ratios and solar wall heating. (March 2021) - Chen, Lan; Hang, Jian; Chen, Guanwen; Liu, Shanhe; Lin, Yuanyuan; Mattsson, Magnus; Sandberg, Mats; Ling, Hong
Abstract: Optimizing urban ventilation is an effective way to improve urban air quality and thermal environment. For this purpose, under the validation of wind-tunnel experiments, flow regimes and micro thermal environment in typical reduced-canyon models with aspect ratios ( AR ) of 1.1, 2.4, 4 and 5.67 were investigated by CFD simulations using periodic boundary condition. ANSYS Fluent 15.0 with a solar ray tracing model and radiation model was performed to numerically study turbulence characteristics with wind-driven force and solar-heating conditions. Results revealed that, with wind-driven condition, a clockwise vortex existed in normal and deep street canyon ( AR = 1.1 and 2.4) while two counter-rotating vortices appeared in extremely deep canyon ( AR = 4 and 5.67). Moreover, different turbulence structures and air temperature distribution existed in canyons with different solar-heating conditions. When the leeward wall or ground was heated, the pedestrian-level velocity increased and street ventilation was strengthened compared to wind-driven condition for all AR values. Particularly, the single main vortex was strengthened ( AR = 1.1 and 2.4), and the two-vortex structure in extremely deep canyons ( AR = 4 and 5.67) changed to single-vortex structure. When the windward wall was heated, the clockwise main vortex at AR = 1.1 and 2.4 was deformed, and a new sub vortex gradually appeared near street bottom. Furthermore, at AR = 4 and 5.67, windward solar heating destroyed the two-vortex structure and slightly improved pollutant dilution capacity. This work implied that extremely deep street design with weak pedestrian-level ventilation should be avoided. It also provides a meaningful reference for urban planning. Highlights: Wind/thermal environment in 2D scaled street canyons ( H/W = AR = 1.1–5.67) were studied. In neutral case, two vortices (or one vortex) appear at AR = 4, 5.67 (or 1.1, 2.4). At H/W = 4/5.67, solar heating destroys two-vortex flow/raises its poor ventilation. At AR = 1.1/2.4, ground/leeward solar heating enhance single vortex and ventilation. At AR = 1.1/2.4, windward heating induces two vortexes and worse pollutant dilution.